Influence of tows waviness and anisotropy on effective Mode I fracture toughness of triaxially woven fabric composites. (September 2017) - Al-Fasih, M.Y.; Kueh, A.B.H.; Abo Sabah, S.H.; Yahya, M.Y.
Highlights: Waviness and anisotropy effects on fracture toughness ( K IC ) of TWF are studied. 2D isotropic Kagome, wavy isotropic TWF, and wavy anisotropic TWF are modeled. K IC increases with relative density, the inverse of cell size, and crack length. Both waviness and anisotropy of tows cause a drop in K IC (up to a maximum of 76%). K IC reduction is strongly affected by tow waviness, but less sensitive to its anisotropy. Abstract: Tows waviness and anisotropy effects on effective Mode I fracture toughness, K IC, of triaxially woven fabric (TWF) composite were numerically and experimentally investigated. 2D isotropic Kagome, wavy isotropic, and wavy anisotropic TWF were modeled for various relative densities, crack lengths, and cell sizes, verification of which was ensured with experimental results. In general, K IC increases with relative density, the inverse of cell size, and crack length. Both waviness and anisotropy cause a drop in K IC, with a remarkable 76% of maximum knockdown in comparison to those without these effects. K IC reduction is observed to be highly sensitive to tows waviness. The influence of tows anisotropy on K IC reduction of TWF composites is somewhat minor, compared to TWF with wavy isotropic members.